Measuring the Impact of Sustainable Management Practices on Organizational Performance - Chomsiri Yada Kurusatienkit (Journal of Management and Administration Provision, 2022)
The effects of environmentally responsible administration on business effectiveness are the focus of this analysis. Combining quantitative poll data from 200 managers across sectors with qualitative case study analysis was the methodology we settled on. The poll responses were analyzed using descriptive statistics, and the premise that sustainable management techniques improve corporate performance was tested using inferential statistics. Case study analysis's anecdotal data added to our understanding of how sustainable management practices boost productivity in businesses. Sustainable management techniques were discovered to have a statistically substantial, favorable association with business success. Sustainable management techniques were found to have a positive effect on company success. By analyzing case studies qualitatively, we learned that sustainable management practices can boost corporate performance in a number of ways, including through increased employee involvement, strengthened partner relationships, and a more reputable brand. Our research suggests that ecological management techniques can have a major impact on business success. These results have substantial ramifications for managers and lawmakers alike, as sustainable management practices can be an effective means for businesses to boost performance and obtain an edge in the market. In order to better understand the connection between sustainable management practices and enhanced organizational performance, future studies will need to use a larger group and focus on the particular processes by which these practices work.